Tra Archeologia e Archeometria Uno studio archeometrico e storico-economico di alcune ceramiche provenienti dai Monti Sicani e dalla chora di Camarina - Pendolino, Federica (Universitätsverlag Göttingen, 2023)
In this research work, an archaeometric study was carried out on 374 pottery samples (prehistoric, indigenous, black-painted, kitchenware, amphorae, Terra Sigillata, and Tegole) from two archaeological areas in Sicily: The Sicani Mountains and the chora of Camarina. For this purpose, The ceramic fractions were analyzed by particle-induced X-ray emission (PIXE). This form of analysis proved to be crucial, as it permitted the comparison of the find materials studied in this thesis and the data obtained from the scientific literature through multivariate statistical analysis. This made it possible to identify the place of production of the finds, distin-guish local materials from imported ones, and reflect on their circulation in Sicily, in a regional and interregional framework. Data processing also highlighted the evolution of regional economic exchanges in Sicily, allowing a reconstruction of some trade circuits.